DETERMINAN KEJADIAN HIPERTENSI DI PUSKESMAS KECAMATAN TAMANSARI KOTA JAKARTA BARAT - Sofia Qorina; Alib Birwin; Rony Darmawansyah Alnur (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Hypertension or high blood pressure is a rise in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Based on the data in Tamansari Community Health Center, West Jakarta City, Hypertension becomes the first of the tenth diseases found there. This study aims to know the factors related to Hypertension in Tamansari Community Health Center, West Jakarta City. The study design of this study is a case-control study design. Fifty samples were taken in each group case-control with the Non-Probability Sampling technique, Accidental Sampling. The data is analyzed using the Chi-Square test. The result of the univariate analysis shows respondent proportion >40 years old (58%), gender (49%), family history (67%), obesity (61%), lack of physical activity (50%), smoking habit (37%), and excessive consumption of atrium (41%). The bivariate test result shows related variables to Hypertension are age, gender, family history, physical activity, and atrium consumption. While unrelated variables are obesity, smoking habit, and alcohol consumption. Tamansari Community Health Center, West Jakarta City, should improve its promotive program, such as health counseling about hypertension risk factors, to the public to prevent and reduce Hypertension.